2016
DOI: 10.1177/0306624x16657622
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Religiosity and Deviance Among Adolescents in a Religiously Pluralistic Society

Abstract: Most empirical studies of religion and deviance have employed samples from Western countries, especially the United States, where one predominant religion-Judeo-Christianity-is an embedded fixture of the mainstream culture. By comparison, research conducted in East Asia, where religious pluralism is the norm rather than the exception, is extremely scarce. Moreover, a large proportion of the population in East Asia professes themselves to be atheists. Given the drastically different religious climates between E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These differences in sociosexuality may be explained by the fact that sexuality in Buddhism is not formally associated with sin [46]. More recent studies have found that, in South-Korea, Buddhist religiosity does not prevent morally deviant behaviors such as delinquency or drinking [47].…”
Section: Morality and Valuesmentioning
confidence: 98%
“…These differences in sociosexuality may be explained by the fact that sexuality in Buddhism is not formally associated with sin [46]. More recent studies have found that, in South-Korea, Buddhist religiosity does not prevent morally deviant behaviors such as delinquency or drinking [47].…”
Section: Morality and Valuesmentioning
confidence: 98%
“…Much has been written about the link between religion and crime, and the widespread assumption is that religiosity may decrease or prevent criminality, while strengthening pro-social behaviors (Dodson et al, 2011;Harris et al, 2017;Sturgis and Baller, 2012;Yun and Lee, 2016). Overall, the religious framework may provide released prisoners with social support systems, help them to reenter society and renew their social ties, and assist them in finding a job, home, and so on (Stansfield et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the history of corrections, religion and its institutions played a key role in shaping punishment and rehabilitation of offenders (Clear, Hardyman, Stout, Lucken, and Dammer, 2000;Johnson, 2004;Morag and Teman, 2018;Ronel, 2015;Ronel and Ben-Yair, 2017;Schaefer, Sams, and Lux, 2016;Wilson, 2016;Yun and Lee, 2016). Within this perspective, offenders are viewed as morally flawed, and the pursuit of moral and spiritual correction of their souls through atonement, work, obedience, and prayer -are common practices in the rehabilitating of offenders (Dodson et al, 2011;Ronel and Ben-Yair, 2017;Schaefer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies tend to fall along two lines, either confirming the irrelevance of religion and deviance (Cochran & Akers, 1989;Tittle & Welch, 1983;Welch, Tittle, & Grasmick, 2006), or pointing out certain inhibiting effect of religiosity depending on the types of religious contexts (Benda, 2002;Corcoran, Pettinicchio, & Robbins, 2012;Evans, Cullen, Dunaway, & Burton Jr, 1995;Rohrbaugh & Jessor, 2017). Additional studies have looked at religious contexts beyond the WEIRD (Western, educated, industrialized, rich, democratic) countries such as in South Korea and China but also reached inconsistent results on the religiosity-deviance relationship (Wang & Jang, 2018;Yun & Lee, 2016).…”
Section: The Relationship Between Religions and Lying Or Violencementioning
confidence: 99%